Discursos do risível e do riso numa visão socio-cognitiva - Nélo, Maria José (2011)
This thesis aims 1) generally at contributing studies on the laughable and laughter both in verbal texts and texts expressed by semiotic means other than the multimodal ones; and, 2) more specifically at examining whether the laughable is a discursive or textual genre; at identifying the functions and actions performed by the speaker and interlocutor as participants of a discursive context; at evaluating the argumentative strategies used by the speaker, who, intending to secure the interlocutor s laughter causes him/her to accept a new opinion; at investigating the intersection of the intertexts and interdiscourses in the production of the laughable and laughter. In considering that both laughter and the laughable have been dealt with in uni and interdisciplinarity, this thesis places both laughter and the laughable in the intersection of intertexts and interdiscourses, forming an integrative view, once it is crucial to tackle them by a muldisciplinary view, viewing the cognitive sciences as transdisciplinarity. Thus, an integrative model was chosen, so as to discuss enunciative, textual, discursive, historic, interactional, anatomical/physiological and cultural aspects.In this sense, this research has adopted the following methodological procedures: 1) theoretical/analytical procedure: theoretical review of the different treatments given to laughter and the laughable, besides other studies concerning text and discourse, with socio-interactional point of view; 2) selection of the corpora; the material selected for the analysis comprises jokes, stories, chronicles of daily life and editorial cartoons. The findings suggest that intertexts and interdiscourses form the actions which integrate the illocutionary act provoking laughter with the perlocutionary act of the one who laughs